The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1080/01688639208402543
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive rehabilitation of the hemineglect disorder in chronic patients with unilateral right brain damage

Abstract: Thirteen patients with a stabilized hemineglect symptomatology due to right-hemisphere lesions were subjected to a rehabilitation training specifically aimed at reducing the scanning deficit. The training consisted of four procedures (visual-spatial scanning, reading and copying training, copying of line drawings on a dot matrix, and figure description) which lasted 40 sessions. By the end of therapy, the patients as a group showed significant improvements on several standard tests of hemineglect. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
104
0
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 237 publications
(116 citation statements)
references
References 22 publications
5
104
0
6
Order By: Relevance
“…Consistent with previous observations (Friedrieh and Margolin, 1993;Posner et al, 1984), the present study shows that RT testing may reveal a residual spatial bias in patients who had recovered from neglect. The serial analysis of response latencies demonstrated that this residual bias mainly affected the initial phase of the task.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with previous observations (Friedrieh and Margolin, 1993;Posner et al, 1984), the present study shows that RT testing may reveal a residual spatial bias in patients who had recovered from neglect. The serial analysis of response latencies demonstrated that this residual bias mainly affected the initial phase of the task.…”
Section: Discussionsupporting
confidence: 93%
“…If the observer voluntarily attends to a stimulus, an abrupt onset at another spatial location is not able to capture his or her attention. These observations fit in a hierarchical model of attentional orienting (see Posner and Petersen, 1990), in which a frontal system, more concerned with volitional orienting, controls more posterior areas, which are in turn responsible for automatic, stimulus-driven orienting. When the anterior system is not employed, then an abrupt onset automatically captures attention through the activation of the posterior system.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations